Participación ciudadana, patrimonialistas y gestión del patrimonio cultural inmueble precolonial del Perú - Alexandrino Ocaña, Grace (Pontificia Universidad Católica del Perú, 2023)
For over ten years, Peru has seen the rise of groups of citizens who want to take over the responsibility for the safeguard[1]ing of the nation’s pre-colonial cultural heritage. Citizen participation in the safeguard of heritage has not been much implemented despite its inclusion in the legal regulations laid down by the Peruvian government. Even more, Peru’s authorities and cultural experts still favour a material-centred preservation outlook over the social use and the interac[1]tion between contemporary societies and the built heritage. Based on an extensive ethnographic and archival work, I here characterize what citizen participation in the management of pre-Colonial structures has been like since the estab[1]lishment of the Ministry of Culture; describe the way in which citizen participation has developed ever since cultural heritage grassroots organizations appeared; and discuss the potential that citizen participation holds for the attainment of a more sustainable management of heritage.

Desde hace más de diez años existen grupos de ciudadanas y ciudadanos peruanos que buscan asumir responsabilidad por el cuidado del patrimonio cultural precolonial del Perú. A pesar que la participación ciudadana en la salvaguarda del patrimonio está prevista en las regulaciones legales del gobierno peruano, esta figura está poco implementada. Más aún, las autoridades y expertos culturales del país todavía favorecen una perspectiva de preservación centrada en los materiales y no en el uso social y la interacción entre sociedades contemporáneas y patrimonio mueble. Basándome en un extenso trabajo etnográfico y de archivo, en este artículo caracterizo cómo ha sido la participación ciudadana en la gestión del patrimonio inmueble precolonial desde la creación del Ministerio de Cultura, describo el modo en que se ha dado la participación ciudadana desde la aparición de grupos patrimonialistas y reflexiono sobre las posibilidades que la participación ciudadana ofrece para alcanzar una gestión del patrimonio más sostenible.
Keywords: Citizen participation; Heritage grassroots organizations; HGROs; Cultural heritage management; Precolonial immovable heritage; participación ciudadana; patrimonialistas; gestión del patrimonio cultural; patrimonio inmueble precolonial; Ministerio de Cultura; https://purl.org/pe-repo/ocde/ford#6.01.02